Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/jth.14284
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial calcium uniporter regulates procoagulant platelet formation

Abstract: Essentials Mitochondrial hyperpolarization enhances the conversion of platelets to a procoagulant phenotype. Mitochondrial calcium uniporter (MCU) function is essential in procoagulant platelet formation. Mitochondrial calcium uniporter deletion does not impact other aspects of platelet activation. Ablation of MCU results in the emergence of a permeability transition pore-independent pathway. SUMMARY: Background Procoagulant platelets comprise a phenotypically distinct subpopulation of activated platelets with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 27 publications
3
36
0
Order By: Relevance
“…7). 41,50 Understanding the role of NCX in the platelet procoagulant activity and signaling implicated upstream of NCX directionality may reveal important What is known about this topic?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7). 41,50 Understanding the role of NCX in the platelet procoagulant activity and signaling implicated upstream of NCX directionality may reveal important What is known about this topic?…”
Section: Resultsmentioning
confidence: 99%
“…Recent publications reported that high and sustained calcium mobilization during procoagulant response triggers mitochondrial calcium influx, which is responsible for mitochondrial potential loss, mitochondrial permeability transition pore (mPTP) formation, and eventually exposure of PS. 41 Therefore, delayed PS exposure (►Fig. 3A), delayed loss of mitochondrial potential (►Fig.…”
Section: Thrombosis and Haemostasismentioning
confidence: 99%
“…13 Jobe et al have demonstrated some of the pathways involved in the creation of this phenotype, specifically the Fcγ receptor extracellularly and the mitochondrial calcium uptake channel intracellularly. 14,15 Several studies support this activation and exhaustion phenotype during TIC. Platelets sampled after trauma can express markers of cellular activation in addition to the broad functional impairments mentioned previously.…”
Section: Platelets In Trauma-induced Coagulopathymentioning
confidence: 92%
“…The intracellular Ca 2+ is taken up by the mitochondria via the mitochondrial calcium uniporter. The increasing mitochondrial Ca 2+ level eventually lead to the opening of the mPTP [89][90][91]. Whether the opening of the mPTP results in the release of additional Ca 2+ which induces a procoagulant response, or whether the mPTP has another mechanism of action is currently unknown [90].…”
mentioning
confidence: 99%
“…The increasing mitochondrial Ca 2+ level eventually lead to the opening of the mPTP [89][90][91]. Whether the opening of the mPTP results in the release of additional Ca 2+ which induces a procoagulant response, or whether the mPTP has another mechanism of action is currently unknown [90]. The lack of impact of mPTP inhibition seen upon platelet stimulation with the Ca 2+ -ionophore A23187 [87,88] suggests that the intracellular Ca 2+ concentration is the important trigger.…”
mentioning
confidence: 99%